KOMPOSISI VEGETASI DI KAWASAN HUTAN LINDUNG BATUKARU (RTK.4 : Desa Gesing, Kec. Banjar - Buleleng dan Desa Bukit Catu, Kec. Baturiti - Tabanan) - I Gusti Alit Gunadi (Bumi Lestari Journal of Environment)
The purposes of the research are to know the composition, distribution, and dominantspecies of vegetation at Batukaru forest conservation area (RTK-4). This research usedtransect method done by systematic plot sampling. Five transects were made, that was thedistance of 1 km each transect line. In each transect line there were 10 plots with the dictanceof 100 m each plot.The result of the experiment found 33 kinds of higher plant to cover the field on Gesingvillage and 18 kinds on Bukit Catu village, with Podocarpus imbricatus Blume is thedominant species on the both villages, with each the important value index of 88,82 % and99,47 % for the higher plant, so that species not stable yet. The lower vegetations thatidentificated on each location are 27 and 34 kinds of speciesDiversity Index on some level of plant growth at Gesing and Bukit Catu villages arearound 1,88 (sedling) – 2,77 (tree) and 1,77 (sedling) – 2,11 (tree), so the communitycondition is in the term of stable.